Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 52790 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Molossus coibensis J.A.Allen, 1904", "TaxonKey is Eumops underwoodi Goodwin, 1940", "TaxonKey is Eumops perotis (Schinz, 1821)", "TaxonKey is Promops centralis Thomas, 1915", "TaxonKey is Molossus aztecus Saussure, 1860", "TaxonKey is Eumops hansae Sanborn, 1932", "TaxonKey is Molossus rufus E.Geoffroy, 1805", "TaxonKey is Nyctinomops macrotis (Gray, 1840)", "TaxonKey is Molossus sinaloae J.A.Allen, 1906", "TaxonKey is Nyctinomops laticaudatus (E.Geoffroy, 1805)", "TaxonKey is Cynomops mexicanus (Jones & Genoways, 1967)", "TaxonKey is Nyctinomops aurispinosus (Peale, 1848)", "TaxonKey is Tadarida brasiliensis (I.Geoffroy, 1824)", "TaxonKey is Eumops auripendulus (Shaw, 1800)", "TaxonKey is Nyctinomops femorosaccus (Merriam, 1889)", "TaxonKey is Eumops bonariensis nanus (Miller, 1900)", "TaxonKey is Molossus molossus (Pallas, 1766)" ] } The dataset includes 52790 records from 137 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000233-150827100048397/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences